1035325 Studi Deskriptif Sikap dan Pengetahuan Ibu Terhadap Perawatan Tali Pusat Pada Bayi Baru Lahir - Juliana Widyastuti Wahyuningsih (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
Abstract In general, the newborn's umbilical cord will collapse or fall off within one to three weeks after birth. As long as it is not separated, the baby's parents need to keep the area clean and dry. This is caused by wet and humid conditions that can increase the growth of germs that cause infection. The lack of good attitude and good knowledge of puerperal mothers for umbilical cord care in newborns makes researchers interested in conducting research. Newborns in Sukajaya Village, Sukarame District Palembang ". This research is a descriptive study with cross-sectional design. The population and sample in this study were mothers who had babies aged 0-14 days in Sukajaya Village, Sukarame District, Palembang, amounting to 40 people. Research conducted in August 2019. Based on the results of this study it can be concluded that the majority of mothers have good knowledge which is equal to 55% and more about mothers in performing cord care that is already good at 80%. Keywords: umbilical cord, Newborns